Radiocarbon monoxide indicates increasing atmospheric oxidizing capacity - Olaf Morgenstern; Rowena Moss; Martin Manning; Guang Zeng; Hinrich Schaefer; Ilya Usoskin; Jocelyn Turnbull; Gordon Brailsford; Sylvia Nichol; Tony Bromley (Nature Communications)
Abstract Hydroxyl (OH) is the atmosphere’s main oxidant removing most pollutants including methane. Its short lifetime prevents large-scale direct observational quantification. Abundances inferred using anthropogenic trace gas measurements and models yield conflicting trend estimates. By contrast, radiocarbon monoxide (14CO), produced naturally by cosmic rays and almost exclusively removed by OH, is a tracer with a well-understood source. Here we show that Southern-Hemisphere 14CO measurements indicate increasing OH. New Zealand 14CO data exhibit an annual-mean decrease of 12 ± 2% since 1997, whereas Antarctic measurements show a December-January decrease of 43 ± 24%. Both imply similar OH increases, corroborating our own and other model results suggesting that OH has been globally increasing during recent decades. Model sensitivity simulations illustrate the roles of methane, nitrogen oxides, stratospheric ozone depletion, and global warming driving these trends. They have substantial implications for the budgets of pollutants removed by OH, and especially imply larger than documented methane emission increases.